Clinical characteristics and suicidal ideation as predictors of suicide: prospective study of 1000 referrals to general adult psychiatry - David Hayward; Blair Johnston; Donald J. MacIntyre; Douglas Steele (BJPsych Bulletin)
Aims and method Questions often follow the suicide of someone who presented to general adult psychiatry (GAP) when expressing suicidal thoughts: ‘Why were they not admitted, or managed differently, when they said they were suicidal?’ Answering these questions requires knowledge of the prevalence of suicidal ideation in patients presenting to GAP. Therefore, we determined the general clinical characteristics, including suicidal ideation, of a large sample of patients presenting to a GAP emergency assessment service or referred as non-emergencies to a GAP service.